2014
DOI: 10.1016/j.jallcom.2014.07.140
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation and thermodynamic calculations of the Cu–In–Ni phase diagram

Abstract: a b s t r a c tPhase diagram of the Cu-In-Ni ternary system was investigated using differential thermal analysis (DTA), scanning electron microscopy (SEM) with energy dispersive spectrometry (EDS), and X-ray powder diffraction (XRD) methods. Experimentally obtained results were compared with the results of thermodynamic calculation of phase equilibria based on calculation of phase diagram (CALPHAD) method and literature data. Phase transition temperatures of alloys with overall compositions along three selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 74 publications
1
3
0
Order By: Relevance
“…This topic has rarely been studied in the literature. Minic et al [44] reported that Cu-Ni-In ternary system contains several intermetallic compounds as confirmed in the experimental results. Phase transitions occurred on the ternary alloy samples by the reduction temperature because of the dominant effect on the crystallographic orientation, and the residence time of the aerosol/particle in the reaction zone.…”
Section: Cuniin Alloy Particlessupporting
confidence: 67%
See 1 more Smart Citation
“…This topic has rarely been studied in the literature. Minic et al [44] reported that Cu-Ni-In ternary system contains several intermetallic compounds as confirmed in the experimental results. Phase transitions occurred on the ternary alloy samples by the reduction temperature because of the dominant effect on the crystallographic orientation, and the residence time of the aerosol/particle in the reaction zone.…”
Section: Cuniin Alloy Particlessupporting
confidence: 67%
“…However, a miscibility gap in the solid-state Cu-Ni in solution also exists at low temperatures. [44] The experimentally obtained diffraction peaks correspond with the three Figure 3 shows the EDS spectrum of nanostructured CuNi alloy particles produced at elevating reduction temperatures. The experimentally obtained atomic percentages of Cu and Ni in the samples are given in Table II.…”
Section: B Structural and Morphological Characterizationmentioning
confidence: 67%
“…The Cu-In-Ni ternary system has been previously experimentally and thermodynamically assessed by Minic et al 15 . In their study, Minic et al 15 reported the liquidus surface, three vertical sections and isothermal sections at 400 ºC and 500 ºC.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that Cu and Cu based alloys are very important for electronic industry. In addition to good electrical and thermal conductivity and corrosion resistance [1][2][3][4][5][6][7] it is significant that all used copper is recyclable without any loss of quality. Also copper can easily make alloys with a variety of elements [8][9][10].…”
Section: Introductionmentioning
confidence: 99%